ENHANCING EFL STUDENTS’ SPEAKING PROFICIENCY THROUGH TASK-BASED LEARNING: A ROLE-PLAY APPROACH - Dildora Mukhammadjonova (PEDAGOGS, 2025)
Abstract. This study examines the effectiveness of task-based instruction (TBI) in improving the speaking skills of intermediate-level English as a Foreign Language (EFL) students at Uzbekistan State World Languages University. Specifically, it explores how role-plays, as a TBI method, contribute to fluency, accuracy, and confidence in spoken English. The research compares students’ speaking proficiency before and after the implementation of TBI. The results indicate that role-plays significantly enhance students’ ability to communicate in English. The findings suggest that task-based approaches should be integrated into EFL curriculum to foster effective oral communication skills.